Vitamin D Receptor Gene Polymorphism and Asthma in Southern Iran - Bijanzadeh, Mahdi; Sharifbakhsh, Shiva; Keshavarzi, Fatemeh; Asl, Javad M. (Current Respiratory Medicine Reviews, 2018)
Background: Asthma is a multifactorial genetic disease caused by the interaction between genetic and environmental factors. FokI is a polymorphic site in exon II at the 5’ end of the vitamin D receptor gene locus on chromosome 12q13 and can be identified using the FokI restriction enzyme. It has an extensive promoter region capable of generating multiple tissue-specific transcripts, and lies just downstream from the collagen type II alpha1 gene. Objective: The main aim of this study was evaluation of VDR FokI polymorphism as a biomarker for detection of high-risk persons to express clinical manifestation of asthma, after exposure to environmental triggers. Methods: In the present case-control study, we analyzed FokI polymorphism in 50 doctor confirmed asthmatic patients and 50 healthy controls by Polymerase Chain Reaction (PCR) amplification and Restriction Fragment Length Polymorphism (RFLP). The data were analyzed using SPSS software version 16. Results: The significant differences were observed for the FokI T>C (rs10735810) polymorphism in asthmatic patients in comparison with controls (p<0.001). This relationship exists without considering the sex and age of cases and controls. The significant association of asthma with FokI SNP (single nucleotide polymorphisms) compared with healthy controls, was presented for the first time in the Iranian population. Conclusion: The significant association of asthma with FokI SNP polymorphisms compared with healthy controls, was presented for the first time in the Iranian population. Introducing of this candidate gene can help the development of diagnostic and interventional strategies that are safe, effective, necessary and individualized for asthmatic patients.
Keywords: restriction enzyme